2015
DOI: 10.1177/1059601115578027
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Positive and Building Strength

Abstract: During an organizational crisis in health care, we collected multilevel data from 426 team members and 52 leaders. The results of hierarchical linear modeling describe the influence of leader behavior on team members' resilience, which is primarily through affective mechanisms. Specifically, transformational leadership was associated with greater levels of positive affect and lower levels of negative affect, which in turn predicted higher resilience among team members. Inverse effects were found for the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 85 publications
(158 reference statements)
1
76
0
5
Order By: Relevance
“…These studies argue that relationships at work can be an important source of strength, offer support, and hence increase individual resilience. Examples of factors that are studied in this respect are: support from others (Meneghel, Borgogni, Miraglia, Salanova, & Martinez, 2016;Jensen, Trollope-Kumar, Waters, & Everson, 2008), relationship with the supervisor (Peters & Pearce, 2012) and transformational leadership (Harland et al, 2005;Sommer, Howell, & Hadley, 2016). In general, these prior findings demonstrate the importance of high-quality relations between employees and their supervisor for employee well-being and resilience.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies argue that relationships at work can be an important source of strength, offer support, and hence increase individual resilience. Examples of factors that are studied in this respect are: support from others (Meneghel, Borgogni, Miraglia, Salanova, & Martinez, 2016;Jensen, Trollope-Kumar, Waters, & Everson, 2008), relationship with the supervisor (Peters & Pearce, 2012) and transformational leadership (Harland et al, 2005;Sommer, Howell, & Hadley, 2016). In general, these prior findings demonstrate the importance of high-quality relations between employees and their supervisor for employee well-being and resilience.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 95%
“…For example, in a qualitative study about early career teacher resilience, Peters and Pearce (2012) found that the relationship with principals has a large influence (negative and positive) on teachers' feelings of personal and professional well-being. A quantitative study among health care teams by Sommer et al (2016) establishes the positive influence of transformational leadership on team members' resilience. Similarly, Kuntz, Connell, et al (2017) found that the availability of support and feedback was positively related to individual resilient behaviour.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The second was the commitment to the organization as an extension of employees' personal value systems. According to the theory of transformational leadership, when an organizational leader taps into individuals' morals and values and engages them in a collective vision, a lasting, sustainable transformation is created, which is characteristic of a resilient organization [31,32].…”
Section: Servant and Transformational Leadershipmentioning
confidence: 99%
“…In these organizations, hope and optimism appeared to be how organizational members made sense of change, informed their responses, and contributed to resilience [32]. This framework resulted in organizational members who were cognitively prepared to adapt to the many changes that affected the organizations.…”
Section: Another Participant Statedmentioning
confidence: 99%
“…If team leaders and/or team members themselves can coordinate their interaction processes to increase their own and others' positive energy, they might also increase efforts in subsequent team activities. Such upward spirals might lead not only to improved team performance but also to team members' greater well-being (e.g., Fredrickson & Branigan, 2005;Sommer, Howell, & Hadley, 2015).…”
Section: Managerial Implicationsmentioning
confidence: 99%